Myxoid Inflammatory Myofibroblastic Sarcoma: Clinicopathologic Analysis of 25 Cases of a Distinctive Sarcoma With Deceptively Bland Morphology and Aggressive Clinical Behavior - Papke, David J.; Odintsov, Igor; Dickson, Brendan C.; Nucci, Marisa R.; Agaimy, Abbas; Fletcher, Christopher D.M. (American Journal of Surgical Pathology, 2024)
The number of recognized sarcoma types harboring targetable molecular alterations continues to increase. Here we present 25 examples of a distinctive myofibroblastic tumor, provisionally termed "myxoid inflammatory myofibroblastic sarcoma,"which might be related to inflammatory myofibroblastic tumor, and which occurred in 13 males (52%) and 12 females at a median age of 37 years (range: 7 to 79 years). Primary tumor sites were peritoneum (18 patients; 72%), paratesticular (2; 8%), chest wall (1), upper extremity (1), esophagus (1), retroperitoneum (1), and uterus (1). Nine peritoneal tumors (50%) were multifocal at presentation; all other tumors were unifocal. Tumors showed bland-to-mildly-atypical neoplastic myofibroblasts in a myxoid stroma, with prominent inflammatory infiltrates in 22 cases (88%). Most tumors showed delicate branching stromal vessels like those of myxoid liposarcoma, and most showed infiltrative growth through non-neoplastic tissue. Immunohistochemistry demonstrated expression of SMA (19/25 tumors; 76%), desmin (13/22; 59%), and CD30 (5/11; 45%), while ALK was expressed in 1 tumor (of 25; 4%) that was negative for ALK rearrangement. Sequencing of 11 tumors showed seven to harbor tyrosine kinase fusions (4 PDGFRB, 2 PML::JAK1, 1 SEC31A::PDGFRA). Two instead harbored hot spot KRAS mutations (G12V and Q61H), and 2 were negative for known driving alterations. Clinical follow-up was available for 18 patients (72%; median: 2.7 years; range: 4 mo-12.3 years). Nine patients (50%) were alive with no evidence of disease, 5 (28%) died of disease, and 4 (22%) were alive with disease. Seven patients (39%) experienced peritoneal relapse or distant metastasis. Two patients showed disease progression on conventional, nontargeted chemotherapy. The patient whose tumor harbored SEC31A::PDGFRA was treated after multiple relapses with imatinib and sunitinib therapy, with progression-free periods of 5 and 2 years, respectively. Despite its bland appearance, myxoid inflammatory myofibroblastic sarcoma harbors a significant risk for disseminated disease, particularly when it occurs in the peritoneum. Targeted therapy could be considered for patients with disseminated disease.
CRIS-Team Scopus Importer:2024-07-26
Keywords: JAK1; KRAS; myxoid inflammatory myofibroblastic sarcoma; PDGFRA; PDGFRB; PML